Challenges In Tough Times: Portrait of Stress on Housewives and Mother with Dual Role - Maria Prima Novita; Arthur Huwae (Kuras Institute, 2023)
The COVID-19 pandemic has resulted in mothers taking on additional responsibilities for their children's at-home learning, leading to increased stress levels. This study aimed to determine the differences in maternal stress levels between housewives and mothers with multiple roles during the pandemic. A comparative quantitative method was used with 200 participants (100 housewives and 100 mothers with multiple roles), who were selected through snowball sampling and assessed using the Perceived Stress Scale. The results showed no significant difference in stress levels between the two groups. This suggests that the stress experienced is a common concern for both housewives and mothers with multiple roles, and poses a risk to their mental health during the pandemic. This study highlights the need for support and resources to help mothers manage stress during the COVID-19 pandemic. Recommendations for future research could include exploring specific stressors experienced by each group and developing targeted interventions to support maternal mental health. Additionally, it may be useful to evaluate the long-term impacts of the pandemic on maternal stress levels and the potential for resilience and recovery.